2018
DOI: 10.1002/admi.201700819
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically Mediated Topographic Steering of Neurite Behaviors and Network Formation

Abstract: The relationship between different mechanoregulatory factors and mechanisms by which neuronal development is regulated by diverse biophysical cues in the immediate vicinity of neural cells remains sparsely understood. Considering the extreme physical complexity of neuronal niches, it is imperative to look beyond the chemical cues for a holistic understanding in these lines. Here the role of geometrically diverse physical microcues is studied in morphologically regulating neurite branching, direction, growth, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…Although the Young's modulus results for cells grown on PI59/TiO 2 microgrooved surfaces showed to be more sensitive and with noticeable differences, the increase in cellular rigidity can be attributed to the reorganization of the cytoskeleton of bone cells influenced by the geometry and curved topography of the cellular microenvironment, that offers a greater stimulus in the biomechanical response of the cells. This proposal is supported by previous findings that showed the ability of different cell types to reorganize their cytoskeleton components in response to micro‐topographical substrates 63–65 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although the Young's modulus results for cells grown on PI59/TiO 2 microgrooved surfaces showed to be more sensitive and with noticeable differences, the increase in cellular rigidity can be attributed to the reorganization of the cytoskeleton of bone cells influenced by the geometry and curved topography of the cellular microenvironment, that offers a greater stimulus in the biomechanical response of the cells. This proposal is supported by previous findings that showed the ability of different cell types to reorganize their cytoskeleton components in response to micro‐topographical substrates 63–65 …”
Section: Discussionsupporting
confidence: 86%
“…This proposal is supported by previous findings that showed the ability of different cell types to reorganize their cytoskeleton components in response to microtopographical substrates. [63][64][65] In addition to nanoindentation measurements to assess the Young's modulus of osteoblast cells, AFM can also be used for topographic analysis and provide interesting biological data. Previous studies have reported that conformational changes identified on the surface of cell membranes reflects alterations that occur in the cytoplasmic side in consequence of cell adhesion.…”
Section: Interference Of Microgrooved Surface Geometry On the Biomech...mentioning
confidence: 99%
“…Previous in vitro studies have elucidated topographical effects on several neuronal behaviors including neuronal adhesion, [ 13,14 ] neurite outgrowth, [ 15–18 ] and network formation. [ 19,20 ] The interrelation between the direction of neurite elongation and the topographical feature has enormously been studied. [ 21–23 ] The concept of contact guidance has been proposed to explain the direction of neurite elongation depending on the type of neurons and the morphological attributes of topography.…”
Section: Figurementioning
confidence: 99%
“…In particular, geometrical cues including surface roughness, pores, and orientation have been suggested to play an essential role in neuronal growth and circuit formation . Emerging biomaterials and advanced fabrication techniques have advanced geometrical regulation on artificial substrates to guide neuronal cell adhesion, migration, proliferation, and differentiation. To pattern neurons, numerous nano-, micro-, and macrofabrication techniques haven been applied for creating substrates with varying degrees of topology, including photolithography, soft lithography, ion-beam lithography, microcontact printing, electrospinning, 3D printing, etc. Although these studies investigated neurite orientation and pathfinding preferences in micro/nanopatterned surfaces, most of them were based on 2D or 2.5D substrates on which neurons could not form strict 3D networks . However, the neurons are embedded in an extracellular matrix (ECM) that forms a complex 3D network of proteins that provide complex mechanical, biochemical, and physical signals …”
mentioning
confidence: 99%
“…7−10 Although these studies investigated neurite orientation and pathfinding preferences in micro/nanopatterned surfaces, most of them were based on 2D or 2.5D substrates on which neurons could not form strict 3D networks. 11 However, the neurons are embedded in an extracellular matrix (ECM) that forms a complex 3D network of proteins that provide complex mechanical, biochemical, and physical signals. 12 To construct a more physiologically relevant microenvironment in vitro to better mimic the in vivo microenvironment, 3D culture systems, especially scaffold-based 3D assemblies of nerve cells, have been widely developed for overcoming the limitations of 2D cultures.…”
mentioning
confidence: 99%